Dividing the Water, Sharing the Benefits : Lessons from Rural-to-Urban Water Reallocation - Garrick, Dustin; De Stefano, Lucia; Turley, Laura; Jorgensen, Isabel; Aguilar-Barajas, Ismael; Schreiner, Barbara; de Souza Leão, Renata; O’Donnell, Erin; Horne, Avril (World Bank, Washington, DC, 2019)
Rural regions are often seen as key sources of urban water supply, creating pressure for reallocation and potential hotspots of competition for water between cities and agriculture. How effective and equitable is reallocation from rural to urban regions, and what have we learned from the global experience? This synthesis report examines the drivers, processes, politics, and outcomes of reallocation based on a review of the literature and insights from four in-depth case studies where governments have reallocated relatively large volumes of water from rural to urban regions: Melbourne, Australia; Mokopane, South Africa; Monterrey, Mexico; and São Paulo, Brazil. The findings suggest that water reallocation can play an important role in regional development. However, reallocation projects have also been controversial because of distributional conflicts regarding who wins and loses. The concept of benefit sharing, long applied to transboundary river basin management, offers a framework for designing effective and equitable reallocation processes, shifting the focus from dividing the water to sharing the benefits among rural and urban regions. The report identifies seven key lessons for realizing the potential of reallocation and limiting the risks.